Relasi Akal Budi dan Iman dalam Apologetika dan Pewartaan Injil - Kalis Stevanus (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2021)
Abstract. There are still Christians who contrast the relationship between apologetics and the proclamation of the Gospel and the role between common sense and faith in these two fields. This paper was intended to study the relationship between apologetics and evangelization, as well as to look up the significance of the role of common sense and faith in the effective task of apology and evangelization. This discussion used a literature study approach that was descriptive-analytic presented. In this discussion, it could be concluded that apologetics and evangelization are God’s mandates which are absolutely fulfilled by every believer whenever and wherever they are. Meanwhile, common sense and faith are two different but not contradictory things where both have their respective places and roles in the practice of apologetics and evangelization. Without common sense and faith, the practice of apologetics and evangelization cannot be carried out effectively.Abstrak. Dijumpai masih ada orang Kristen yang mempertentangkan apologetika dengan pewartaan Injil dan peran antara akal dan iman di dalam kedua bidang tersebut. Tulisan ini dimaksudkan untuk mengkaji relasi apologetika dan pewartaan Injil, serta signifikansi peran akal budi dan iman di dalam tugas berapologia dan pewartaan Injil secara efektif. Kajian ini menggunakan metode studi literatur yang disajikan secara deskriptif-analitif. Melalui kajian ini dapat disimpulkan bahwa apologetika dan pewartaan Injil merupakan mandat Tuhan yang sifatnya mutlak ditunaikan bagi setiap orang percaya kapan pun dan di mana pun berada. Sedangkan akal budi dan iman adalah dua hal yang berbeda tetapi tidak saling bertentangan, di mana keduanya memiliki tempat dan perannya masing-masing dalam praktik berapologetika dan pewartaan Injil. Tanpa akal budi dan iman, maka praktik apologetika dan pewartaan Injil tidak dapat terlaksana dengan efektif.